COX-1-derived prostaglandin E(2) and EP1 receptors are required for the cerebrovascular dysfunction induced by angiotensin II - Capone, Carmen (2010)
Prostaglandin E(2) (PGE(2) ) EP1 receptors (EP1R) may contribute to hypertension and related end-organ damage. Because of the key role of angiotensin II (AngII) in hypertension, we investigated the role of EP1R in the cerebrovascular alterations induced by AngII. Mice were equipped with a cranial window and cerebral blood flow (CBF) was monitored by laser-Doppler flowmetry. The attenuation in CBF responses to whisker stimulation (−46±4%), and the endothelium-dependent vasodilator acetylcholine (−40±4%) induced by acute administration of AngII (250 ng/kg/min; i.v. for 30–40 min) was not observed after cyclooxygenase-1 or EP1R inhibition, and in cyclooxygenase-1 or EP1-null mice. In contrast, cyclooxygenase-2 inhibition or genetic inactivation did not prevent the attenuation. AngII-induced oxidative stress was not observed after cyclooxygenase-1 or EP1R inhibition, and in EP1R-null mice. PGE(2) reinstated the AngII-induced cerebrovascular dysfunction and oxidative stress after cyclooxygenase-1 inhibition. Brain PGE(2) levels were not increased by AngII and were attenuated by cyclooxygenase-1, but not cyclooxygenase-2 inhibition. The cerebrovascular dysfunction induced by 14 day administration of “slow pressor” doses of AngII (600ng/kg/min) was attenuated by neocortical application of SC51089. Cyclooxygenase-1 immunoreactivity was observed in microglia and EP1R in endothelial cells. We conclude that the cerebrovascular dysfunction induced by AngII requires activation of EP1R by constitutive production of PGE(2) derived from cyclooxygenase-1. The findings provide the first evidence that EP1R are involved in the deleterious cerebrovascular effects of AngII and suggest new therapeutic approaches to counteract them.